Early Treatment with Intranasal Neostigmine Reduces Mortality in a Mouse Model of Naja naja (Indian Cobra) Envenomation - Matthew R. Lewin; Stephen P. Samuel; David S. Wexler; Philip Bickler; Sakthivel Vaiyapuri; Brett D. Mensh (Journal of Tropical Medicine)
Objective. Most snakebite deaths occur prior to hospital arrival; yet inexpensive, effective, and easy to administer out-of-hospital treatments do not exist. Acetylcholinesterase inhibitors can be therapeutic in neurotoxic envenomations when administered intravenously, but nasally delivered drugs could facilitate prehospital therapy for these patients. We tested the feasibility of this idea in experimentally envenomed mice. Methods. Mice received intraperitoneal injections of Naja naja venom 2.5 to 10 times the estimated LD50 and then received 5 μL neostigmine (0.5 mg/mL) or 5 μL normal saline by nasal administration. Animals were observed up to 12 hours and survivors were euthanized. Results. 100% of control mice died. Untreated mice injected with 2.5× LD50 Naja naja died at average 193 minutes after injection, while 10 of 15 (67%) of treated mice survived and were behaviorally normal by 6 hours (P<0.02). In the 5× LD50 group, survival was prolonged from 45 minutes to 196 minutes (P=0.01) and for 10× LD50 mice, survival increased from 30 to 175 minutes (P<0.02). Conclusion. This pilot suggests that intranasal drugs can improve survival and is the first direct demonstration that such an approach is plausible, suggesting means by which treatment could be initiated before reaching the hospital. Further investigation of this approach to neurotoxic and other types of envenomation is warranted.